In vitro mechanism for downregulation of ER‐α expression by epigallocatechin gallate in ER+/PR+ human breast cancer cells. Issue 5 (16th January 2013) - De Amicis, Francesca; Russo, Alessandra; Avena, Paola; Santoro, Marta; Vivacqua, Adele; Bonofiglio, Daniela; Mauro, Loredana; Aquila, Saveria; Tramontano, Donatella; Fuqua, Suzanne AW; Andò, Sebastiano
<x xml:space="preserve">Abstract</x> Scope Exposure of the breast to estrogens and other sex hormones is an important cancer risk factor and estrogen receptor downregulators are attracting significant clinical interest. Epigallocatechin gallate (EGCG), a polyphenolic compound found in green tea, has gained considerable attention for its antitumor properties. Here we aimed to investigate the molecular mechanisms through which EGCG regulates ER‐α expression in ER+ PR+ breast cancer cells. Material and methods Western blotting analysis, real‐time PCR, and transient transfections of deletion fragments of the ER‐α gene promoter show that EGCG downregulates ER‐α protein, mRNA, and gene promoter activity with a concomitant reduction of ER‐α genomic and nongenomic signal. These events occur through p38MAPK/CK2 activation, causing the release from Hsp90 of progesterone receptor B (PR‐B) and its consequent nuclear translocation as evidenced by immunofluorescence studies. EMSA, and ChIP assay reveal that, upon EGCG treatment, PR‐B is recruited at the half‐PRE site on ER‐α promoter. This is concomitant with the formation of a corepressor complex containing NCoR and HDAC1 while RNA polymerase II is displaced. The events are crucially mediated by PR‐B isoform, since they are abrogated with PR‐B siRNA. Conclusion Our data provide evidence for a mechanism by which EGCG downregulates ER‐α and explains the inhibitory action of EGCG on the proliferation of ER+ PR+ cancer cells tested. We suggest that the EGCG/PR‐B signaling should be further exploited for clinical approach.